Effect of Nickel on the Microstructures of Coating in Hot-Dipped Aluminide Steel. Issue 9 (3rd July 2016) - Chen, Xiaochun; Peng, Haoping; Su, Xuping; Liu, Ya; Wu, Changjun; Chen, Hairui
Abstract : Hot-dipping aluminizing of 45 steel was carried out in molten Al baths containing 0.0, 1.0, 3.0, and 5.0 wt.% Ni at 710°C for 10, 120, 300, and 600 s. The coatings were analyzed by x-ray diffraction (XRD) and scanning electron microscope (SEM) equipped with energy-dispersive spectroscopy (EDS) and electron backscatter diffraction (EBSD). The coating hot-dipped in the Al-5Ni bath consisted of an outer Al-Ni topcoat (α-Al, θ-Al3 Fe, Al3 Ni, τ1 -Al9 FeNi), minor τ1 -Al9 FeNi, minor θ-Al3 Fe, and major η-Al5 Fe2 layers, respectively, while no τ1 -Al9 FeNi layer was identified in the coating hot-dipped in the Al-1Ni and Al-3Ni bath. Diffusion path model was introduced to explain this phenomenon. Ni as an alloying element added into Al bath decreased the growth rate of η-Al5 Fe2 layer. The average thickness of η-Al5 Fe2 layer followed the parabolic law in hot-dipping in the Al-5Ni bath. Also, η-Al5 Fe2 had the largest growth rate among the intermetallic layers.